Eleventh graders’ learning experiences through a whatsapp group in EFL. - Vergara Hernández, Angie Kattalina; Bayona Piracún, Jhon Alexander (Corporación Universitaria Minuto de Dios, 2018)
In this twenty first century, it is known that technological advances have been having a notable influence in teenagers’ lifestyle. Actually, researchers have identified a situation in Moderno Engativá School, a private school in Bogota where eleventh graders use their cell phones interacting with social networks and applications throughout their classes. Consequently, instead of avoiding the use of these devices and apps, researchers decided to take advantage of these technological resources and use them as a support for the English class in order to promote different learning experiences and in this way analyzing them. Therefore, the objective of this research project was to analyze students’ learning experiences during the participation in a WhatsApp group in EFL. This qualitative study was an Action Research which generates a cycle on the situation identified. The pedagogical implementation was divided in six activities which involved the four language skills –speaking, writing, listening and reading- using that application in order to provide participants with a learning experience in which they could share and interact with their classmates. Lastly, the instruments chosen to collect data were a focus group implemented at the beginning, journals after each session during the implementation, and finally a questionnaire in which participants expressed the most significant experiences for them in a general way about all the activities developed in the WhatsApp group.
Keywords: WhatsApp in the EFL; Learning Experiences; Interaction; Mobile Learning; Aprendizaje; Aptitud de Aprendizaje; Educación Secundaria